Research or teaching? That is the problem: A narrative inquiry into a Chinese college English teacher’s cognitive development in the teaching-research nexus - Ni, Hui; Wu, Xinxin (Frontiers in Psychology, 2023)
This narrative inquiry traces a Chinese college English teacher’s cognitive transformation in teaching-research nexus in a four-year time from the perspective of socio-cultural theory. Several stories were narrated based on the data of reflective journals, literature reading notes, and interaction notes to show how the participant walked out of the teaching-research contradiction and finally reconstructed her identity. The findings indicate that the college English teacher’s perception of research-teaching nexus developed when she actively exercised her agency to take part in social interactions in a supportive sociocultural environment with the regulation of appropriate mediational tools. The conceptual progress in research-teaching nexus finally contributed to her professional development in both teaching and research. The study aims to give some implications for those non-key universities and their staff on how to effectively promote the teaching-research integration.